New cases of facultative interspecific brood parasitism in Black-winged Stilt (Himantopus himantopus) and Eurasian Coot (Fulica atra) - Stermin Alexandru N. (Sciendo, 2021)
Many hypotheses try to explain the evolution and possible relations between obligate and facultative brood parasitism in birds. To explore this, a large number of observations and data are needed. Our understanding based on the observations of facultative parasitic species published in the literature is less clear compared to the obligate parasitic species. This communication is about three cases of facultative interspecific brood parasitism. Two nests of Black-headed Gull (Chroicocephalus ridibundus) parasite by Eurasian Coot (Fulica atra) and one nest of Pied Avocet (Recurvirostra avosetta) parasite by Black-winged Stilt (Himantopus himantopus). These observations are significant as long as interspecific brood parasitism was frequently described in Gruiformes (Rallidae) but has rarely observed within Charadriiformes.